ASSESSMENT OF HEAT WAVE EVENTS IN A CHANGING CLIMATE OVER NIGERIA. - Elijah Adesanya ADEFISAN & Sani AHMAD (International Journal of Research Science and Management, 2018)
Heat waves have attracted increasing attention in recent years due to their frequent occurrence. The present study investigated the heat wave frequency, duration and magnitude in Nigeria using daily maximum, minimum and mean temperatures over thirty-six weather stations from 1986 to 2015. The excess heat factor (EFF) index was applied in the work to investigate the heat wave characteristics. The index is based on a three-day-averaged daily mean temperature (DMT), and is intended to capture heatwave characteristics as they apply to human health outcomes, although its usefulness is likely to be much broader and with potential for international applicability. It is found that the heat wave frequency, duration and intensity show a sandwich distribution across Nigeria, with high occurrence rates in northern part of the country, where the maximum frequency and duration exceeded 2 times and 9 days per year respectively. The high-value zones of heat wave frequency, duration, and intensity in 1986-2015 were basically concentrated in the middle and northern Nigeria. The strongest heat waves were found in extreme north of the country with the highest frequency. The inter-decadal variation of heat wave frequency, days, and intensity are similar. Decreasing trends were all found from around 1986 to around 2003, and significant increasing trends were observed from around 2007 to 2015. The three years with the highest heat wave intensity and maximum heat wave days all appeared in the last decade, indicating that the heat wave intensity, duration and frequency are increasing in Nigeria.